Tingkat Kepuasan Pengguna Sistem Aplikasi Financial & Accounting Software Fina - Murdiyanto, Dono (Journal of Economics & Business UBS, 2020)
This study aimed to analyze the level of user satisfaction of FINA application system (Financial & Accounting Software) in PT Dagsap Endura Eatore. The motivation of this research are: (1) Considering there are some user complaints regarding this application and (2) there has never been related research applications and users from 2007. As well as getting feedback from the users of the application of FINA. Research includes dimensions of quality: Quality of Work Life Satisfaction, Content, Accuracy, Shape, Ease of Use, Timeliness, Flexible, completeness, system integration and speed of response. In the collection of data, the writer used a questionnaire addressed to the user FINA PT Dagsap Endura Eatore located at Head Office and Sentul Office. Data collection should be conducted by the census, where all users of FINA in PT Dagsap Endura Eatore investigated and be used as an object. This study using metods IKP by comparing the level of performance by the level of importance and used diagrams kartesius use some hel SPSS program to test the Validity and Reliability and make a diagram cartesius. The results showed that application users FINA PT Dagsap Endura Eatore satisfied with the performance of the application. Factors that stands out is of the appearance of the report that can be modified (99 %). However there are several factors that go into quadrant A that needs to be evaluated and improvements in coordination between the user, the company and the support team FINA.